1997
DOI: 10.1038/sj.bmt.1700817
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell contamination of peripheral blood stem cell transplants and bone marrow in high-risk breast cancer patients

Abstract: Summary:therapy and stem cell support appears possible. Peters et al 2,3 reported a 78% overall survival (OS) in this high-risk breast cancer subgroup after high-dose chemotherapy folTwenty-one high-risk patients with primary stage II/III breast cancer were treated with high-dose chemolowed by stem cell support (median follow-up 4.5 years).Gianni et al 4 showed a OS of 78% after 5 years in these therapy comprising etoposide, ifosfamide, carboplatin and epirubicin (VIC-E). Tumor cells of epithelial origin patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 7 publications
3
26
0
1
Order By: Relevance
“…27 Studies that addressed the clinical significance of the reinfusion of tumor cells in the apheresis products as assessed by ICC methods have provided contradictory information. [20][21][22]34,36,51 Interestingly, most studies that analyzed metastatic patients did not find a significant correlation between occult tumor reinfusion and time to progression or overall survival 21,22 while a correlation has been observed more frequently in non-metastatic patients. 20,51 In addition, the majority of patients with metastatic disease developed progression in prior metastatic sites rather than in new locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Studies that addressed the clinical significance of the reinfusion of tumor cells in the apheresis products as assessed by ICC methods have provided contradictory information. [20][21][22]34,36,51 Interestingly, most studies that analyzed metastatic patients did not find a significant correlation between occult tumor reinfusion and time to progression or overall survival 21,22 while a correlation has been observed more frequently in non-metastatic patients. 20,51 In addition, the majority of patients with metastatic disease developed progression in prior metastatic sites rather than in new locations.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22]34,36,51 Interestingly, most studies that analyzed metastatic patients did not find a significant correlation between occult tumor reinfusion and time to progression or overall survival 21,22 while a correlation has been observed more frequently in non-metastatic patients. 20,51 In addition, the majority of patients with metastatic disease developed progression in prior metastatic sites rather than in new locations. Both observations suggest that when we are treating a subgroup of patients with a relatively high and chemoresistant residual tumor burden, the inadequate tumor cytoreduction makes it difficult to detect the potential influence of the infusion of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although the prognostic significance of tumor cells in PBPC collections requires further evaluation, a trend of higher relapse rates in breast cancer patients receiving tumor cell positive PBPC collections has been reported. 7 High-dose chemotherapy with hematopoietic rescue appears promising in the treatment of breast cancer, 10,11 but the presence of contaminating tumor cells in the reinfused hematopoietic cell product remains a concern. Retrovirally mediated gene marking techniques and retrospective clinical trials have demonstrated in patients with acute myelogenous leukemia, neuroblastoma, B cell lymphoma, chronic lymphocytic leukemia, or chronic myelogenous leukemia that reinfusion of contaminating tumor cells present in the BM harvest can contribute to disease relapse in the BM itself or in extramedullary sites.…”
mentioning
confidence: 99%
“…[1][2][3][4] The presence of tumor cells in the BM has been shown to be predictive of relapse in early stage [5][6][7] and advanced stage 8,9 breast cancer patients. In addition, the number of tumor cells identified in the BM has been correlated with shorter disease-free and overall survival.…”
mentioning
confidence: 99%
“…Firstly, ifosfamide can be incorporated into chemotherapy regimens to mobilize PBPCs. [8][9][10][11][12][13][14] Secondly, ifosfamide has some potential 428 advantages over cyclophosphamide. Pre-clinical studies have demonstrated that the unique structural properties of ifosfamide may have a beneficial anti-tumor activity; ifosfamide is an analogue of cyclophosphamide with translocation of a chlorethyl group which provides a more effective DNA cross-linking distance between two independent functional alkylating moieties.…”
mentioning
confidence: 99%